Protests, Knowledge and Agroecological Social Movements. An Approach to the Argentine Case from a Decolonial Perspective (2019-2023) - Soto Pimentel, Verónica (PARTECIPAZIONE E CONFLITTO, 2026)
This article analyzes the knowledge mobilized by agroecological social movements (ASMs) in Argentina between 2019 and 2023 to justify their opposition to agribusiness and to articulate alternative proposals for a socially, economically, and ecologically sustainable food system. Particularly, it examines the conceptual repertoires expressed in public mobilizations to understand how Argentine ASMs interpret agribusiness, sustainability, and social justice, and how these interpretations underpin political proposals advanced through protest. The study adopts a mixed-methods approach, combining a systematic count of ASMs’ public protests from 2019 to 2023 with a qualitative content analysis of press releases and organizational documents. The findings show that, through demands opposing extractive practices, advocating state support for agroecological projects, and calling for access to land, Argentine ASMs mobilize key conceptual repertoires that articulate both critiques of agribusiness and alternative proposals. These repertoires underpin specific political demands and, at times, integrate broader projects grounded in diverse knowledge systems. A decolonial lens illuminates how ASMs conceptualize their opposition to modern/colonial civilizing projects and construct locally grounded alternatives to global challenges. The article contributes to scholarship on political agroecology and social movements, and to dialogue between these fields.